Performance evaluation and its impact on the quality of health services in the Saudi health sector in Riyadh - Alotaibi, Fawaz Abdullah; Almotairi, Ali Suliman; Aalghannam, Ghannam Hoewmel; Alqarni, Abdullah Safar; Gaeed, Noora Farhan (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the performance evaluation and its impact on the quality of health services in the Saudi health sector, and the extent of the impact of performance evaluation on the quality of services in the Saudi government health sector, and the relationship between performance evaluation and the quality of health services. And the interest in the health care provided to them, in addition to the fact that the health sector is one of the main axes of the state in the economic, development and tourism aspect, the health sector is one of the most vital and important sectors, so this sector has received great attention from all countries, whether in terms of increased spending or guidance and control The ongoing study aims to ensure that it continues to perform its role at a high level of efficiency, effectiveness and quality of the health services provided. Therefore, the study problem is summarized in the following main question; What is the impact of performance evaluation on the quality of health services in the Saudi health sector? The study also contributes to providing suggestions and recommendations to officials that contribute to raising the level of performance evaluation and working to increase the quality of health services, by emphasizing the importance of the health sector performance evaluation process, and the study will also contribute to educating workers in the Saudi health sector about the importance of performance evaluation in raising efficiency and increasing the level and quality Health services in the Saudi health sector. The study used the descriptive approach, and the study population included all employees of government hospitals in Riyadh, and the study sample consisted of (383) individuals who were selected by the random sampling method, and the study used the questionnaire as a tool for data collection. In light of the foregoing, the study reached a number of results, the most important of which is the existence of a direct (positive) relationship with statistical significance between the quality of the pharmaceutical care service, performance evaluation and the quality of health services in the Saudi health sector. Governmental health care in the Kingdom of Saudi Arabia. In light of the results, the study recommends that the health sector in the Kingdom of Saudi Arabia should pay attention to the performance evaluation process on an ongoing basis through the development of periodic programs and systems for the evaluation and follow-up process and the use of indicators and standards adopted in the Kingdom. Increasing the efficiency of the performance of health services in the health sector by employing technology and automation for all health sector systems and services. Emphasis on conducting a periodic evaluation of the hospital’s performance in various aspects of health services using indicators for evaluating the efficiency of performance in hospitals.